Penentuan Strategi Pemasaran UMKM menggunakan Analisis SWOT - Moh. Amien Rais; M. Naely Azhad; Ahmad Izzudin (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine and analyze the marketing strategy carried out by MSME Tanocraft Tanoker Ledokombo. The research method used is the SWOT analysis method using a qualitative approach. Data collection techniques carried out by researchers are interviews and direct observation to marketing managers. The data obtained from the data collection is then analyzed using SWOT analysis to find out what are the strengths, weaknesses, opportunities, and threats of the marketing strategy carried out by MSMEs. The results show that the Cartesian diagram shows that MSMEs are in the first quadrant which is aggressive with the implementation of the Growth Oriented Strategy which is a very favorable situation for MSMEs. In conclusion, based on a SWOT analysis, it shows that Tanocraft Tanoker Ledokombo SMEs have the strength so that they can take advantage of existing opportunities. Keywords: SWOT Analysis, Marketing Strategy